2016
DOI: 10.3389/fphar.2016.00388
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Protein–Protein Interactions of Human UDP-Glucuronosyltransferases

Abstract: Mammalian UDP-glucuronosyltransferases (UGTs) catalyze the transfer of glucuronic acid from UDP-glucuronic acid to various xenobiotics and endobiotics. Since UGTs comprise rate-limiting enzymes for metabolism of various compounds, co-administration of UGT-inhibiting drugs and genetic deficiency of UGT genes can cause an increased blood concentration of these compounds. During the last few decades, extensive efforts have been made to advance the understanding of gene structure, function, substrate specificity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 112 publications
(137 reference statements)
2
32
0
Order By: Relevance
“…A crystal structure of the C-terminal domain of human UGT2B7 has also been reported 154 . These studies have provided structural bases for understanding the catalytic mechanism(s) and specificity of UGTs, and also provide a framework for beginning to address the specific features of flavonoid glucuronosyltransferases 155 .…”
Section: ■ Structure-based Design Of Novel Glycosyltransferasesmentioning
confidence: 99%
“…A crystal structure of the C-terminal domain of human UGT2B7 has also been reported 154 . These studies have provided structural bases for understanding the catalytic mechanism(s) and specificity of UGTs, and also provide a framework for beginning to address the specific features of flavonoid glucuronosyltransferases 155 .…”
Section: ■ Structure-based Design Of Novel Glycosyltransferasesmentioning
confidence: 99%
“…While there is ample biophysical evidence to support the existence of UGT dimers (Meech and Mackenzie, 1997 ; Lewis et al, 2011 ; Suzuki et al, 2014 ), the lack of structural data has hampered protein-protein interaction research with this enzyme class. Interestingly, the structural data that does exist for human UGT enzymes, that of a partial UGT2B7 structure, does provide an indication for the presence of homo dimers (Miley et al, 2007 ; Fujiwara et al, 2016 ; Audet-Delage et al, 2017 ). In the asymmetric unit, the C terminus of one monomer packs into the predicted UDPGA binding site of the other monomer (Miley et al, 2007 ).…”
Section: X-ray Crystallographymentioning
confidence: 99%
“…Fluorescence studies have also been useful in the study of the human UGT enzymes (Operana and Tukey, 2007 ; Fujiwara et al, 2016 ; Yuan et al, 2016 ). Turkey et al used FRET to examine UGT1A oligomerization in vivo (Operana and Tukey, 2007 ).…”
Section: Fluorescence Technologiesmentioning
confidence: 99%
“…This model was proposed based on the evidence from the authors’ own results indicating that the majority of bilirubin UGT (UGT1A1) was not exposed to the cytosol, hydropathy plot analysis [ 53 ], and complete cDNA sequences of androsterone UGT [ 54 , 55 ], and rat phenol UGT (UGT1A6) [ 56 ]. Site-directed mutagenesis experiments have also confirmed that the UGT proteins are comprised of two domains, one binding the UDPGA (in the conserved C-terminal part of the protein) and one that presumably confers substrate preference located in the less-well conserved N-terminal region [ 57 ]. The determination of an X-ray crystal structure (1.8-Å resolution) for the C-terminal domain of human UGT2B7 is another strong piece of evidence confirming the presence of a nucleotide-binding site in the C-terminal half of the UGT proteins [ 58 ].…”
Section: Compartmentation Hypothesismentioning
confidence: 99%
“…If the binding sites are luminal as predicted, then the rate of glucuronidation might be constrained by the membrane barrier limiting the access of UDPGA, a highly charged molecule synthesized in the cytoplasmic space [ 59 ], to the reaction center. Although the complete crystal structure of a UGT protein is unsolved, homology modeling has been used to predict the three-dimensional structure [ 57 ]. For example, human UGT1A1 and UGT1A10 were homology-modeled using plant UGT71G1 and UDP-galactose 4-epimerase from Escherichia coli , respectively [ 60 , 61 ].…”
Section: Compartmentation Hypothesismentioning
confidence: 99%